HOMEOBOX2, the paralog of SIX-ROWED SPIKE1/HOMEOBOX1, is dispensable for barley spikelet development - Thirulogachandar, Venkatasubbu; Govind, Geetha; Hensel, Götz; Kale, Sandip M.; Kuhlmann, Markus; Eschen-Lippold, Lennart; Rutten, Twan; Koppolu, Ravi; Rajaraman, Jeyaraman; Palakolanu, Sudhakar Reddy; Seiler, Christiane; Sakuma, Shun; et al. (Oxford University Press, 2024)
The HD-ZIP class I transcription factor Homeobox 1 (HvHOX1), also known as Vulgare Row-type Spike 1 (VRS1) or Six-rowed Spike 1, regulates lateral spikelet fertility in barley (Hordeum vulgare L.). It was shown that HvHOX1 has a high expression only in lateral spikelets, while its paralog HvHOX2 was found to be expressed in different plant organs. Yet, the mechanistic functions of HvHOX1 and HvHOX2 during spikelet development are still fragmentary. Here, we show that compared with HvHOX1, HvHOX2 is more highly conserved across different barley genotypes and Hordeum species, hinting at a possibly vital but still unclarified biological role. Using bimolecular fluorescence complementation, DNA-binding, and transactivation assays, we validate that HvHOX1 and HvHOX2 are bona fide transcriptional activators that may potentially heterodimerize. Accordingly, both genes exhibit similar spatiotemporal expression patterns during spike development and growth, albeit their mRNA levels differ quantitatively. We show that HvHOX1 delays the lateral spikelet meristem differentiation and affects fertility by aborting the reproductive organs. Interestingly, the ancestral relationship of the two genes inferred from their co-expressed gene networks suggested that HvHOX1 and HvHOX2 might play a similar role during barley spikelet development. However, CRISPR-derived mutants of HvHOX1 and HvHOX2 demonstrated the suppressive role of HvHOX1 on lateral spikelets, while the loss of HvHOX2 does not influence spikelet development. Collectively, our study shows that through the suppression of reproductive organs, lateral spikelet fertility is regulated by HvHOX1, whereas HvHOX2 is dispensable for spikelet development in barley.